HUBUNGAN ANTARA RELIGIUSITAS DENGAN PSYCHOLOGICAL WELL BEING DITINJAU DARI BIG FIVE PERSONALITY PADA SISWA SMA NEGERI 6 BINJAI - Azizah Batubara (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2017)
This study aims to determine the relationship between Religiosity and Psychological well being in terms of the Big Five Personality in high school students 6 Binjai. There are two hypotheses proposed in this study, namely, there is a relationship between religiosity and Psychological well being in SMA 6 Binjai students and there is a difference between Psychological well being in terms of big five personality in SMA 6 Binjai students. Analysis of the data used in this research is covariance analysis. This research was conducted at the 6th and XI high school 6 Binjai students in the 2013/2014 academic year. This sample was taken by random sampling method, with a total sample of 85 students from the total population. The analysis used is covariance analysis, because it aims to test the hypothesis of one dependent variable (y), one independent variable (x), and one covariable. Based on the analysis of the data above, it was obtained F = 2395,290 with a significance of 0,000 and p <0.05. Based on these results it is said that there is a relationship between religiosity and Psychological well being on the big five personality. Then obtained F = 1.845, sig 0.128 with p> 0.05 which means that there is no difference in Psychological well being among the five personality types of big five personality.Keywords: Psychological well being, Religiosity, Big Five Personality